Schooling does not influences physical activity level in older people - De Quadros Jr., Antonio Carlos [UNESP]; Lamonato, Anne Caroline Camargo [UNESP]; Gobbi, Sebastião [UNESP] (My University, 2011)
Basic functionality and physical activity level are commonly impaired by aging, and can be influenced by depressive symptoms, global cognitive state and schooling. Purpose: to analyze relationship between schooling and basic functionality, physical activity level, depressive symptoms and global cognitive state in physically active older people. Method: 53 physically active older people, both genders, answered to Physical Activity Level Baecke Questionnaire, Katz Scale of Basic Functionality, Mini-Exam of State Mental and Geriatric Depressive Scale. It was used Spearman coefficient of correlation (p≤0,05). Results: it was found significant correlation only between schooling and global cognitive state; physical activity level, basic functionality and depressive symptoms did not correlate to schooling. Conclusion: schooling did not influence physical activity level, basic functionality or depressive symptoms, but it correlated to global cognitive state, according with literature, exerting a protective function.
Nível de escolaridade não influencia nível de atividade física em idosos
Keywords: Aged; Cognition; Education; Motor activity